Pelatihan Kreatifitas Digital Menggunakan Canva Bagi Anggota Karang Taruna Parangloe - Dolly Indra; Lilis Nur Hayati; Muhammad Haerdiansyah Syahnur; Wahyu Kadri Rahmat Suat; Muhammad Rifky Saputra Scania (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
The community engagement partner for this project is the youth members of Karang Taruna Parangloe, who face challenges due to a lack of digital literacy, particularly in utilizing technology for self-development. This initiative will equip these youth members with graphic design skills using the Canva platform. To achieve this goal, we implemented various approaches, beginning with an initial observation to understand the partner's needs, followed by a session on the importance of digital literacy. After the awareness session, we conducted intensive training in graphic design using Canva. This training was followed by an evaluation session to assess the participants' knowledge improvement. The evaluation was carried out through pretests and posttests with 30 youth members. The training results showed that the trained members of Karang Taruna Parangloe can now independently create graphic designs using Canva. The measurements indicated a significant improvement in their knowledge, with the average pretest score of 66.303 increasing to 82.709 in the posttest, reflecting the effectiveness of this community engagement program.